The influence of botulinum toxin A injections into the calf muscles on genu recurvatum in children with cerebral palsy - Klotz, Matthias C. M.; Wolf, Sebastian Immanuel; Heitzmann, Daniel; Gantz, Simone; Braatz, Frank; Dreher, Thomas (Clinical orthopaedics and related research, 2013)
Background - With cerebral palsy (CP), an equinus deformity may lead to genu recurvatum. Botulinum toxin A (BtA) injection into the calf muscles is a well-accepted treatment for dynamic equinus deformity. - Questions/purposes - The purpose of this study was to determine whether BtA injections into the calf muscles to decrease equinus would decrease coexisting genu recurvatum in children with diplegic CP. - Methods - In a retrospective study, 13 children (mean age, 5 years) with spastic diplegic CP showing equinus and coexisting primary genu recurvatum, who were treated with BtA injections into the calf muscles, were included. Evaluations were done before and 6 and 18 weeks after intervention using three-dimensional gait analysis and clinical examinations according to a standardized protocol. Basic statistical analyses (power analysis, ANOVA) were performed to compare genu recurvatum before treatment and at 6 and 18 weeks after injection with BtA. - Results - During stance phase, maximum ankle dorsiflexion was increased substantially from −3.0° ± 14.3° before to 6.2° ± 14.2° 6 weeks after the injections. Despite this, with the numbers available, the amount of recurvatum in stance did not improve with treatment at either 6 or 18 weeks. There was significant improvement of knee hyperextension during stance phase of 6.2° between baseline and 18 weeks after BtA injection, but a genu recurvatum was still present in most patients. - Conclusions - Despite improvement of ankle dorsiflexion after injection with BtA, genu recurvatum did not show relevant improvement at 6 or 18 weeks after injection with the numbers available. Because knee hyperextension remained in most patients, other factors leading to genu recurvatum should be taken into consideration. In addition, a botulinum toxin-induced weakness of the gastrocnemius may explain why recurvatum gait was not significantly reduced. - Level of Evidence - Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.
Gesehen am 19.03.2021